Gendered Journeys: Women, Migration and Feminist Psychology - Espín, Oliva M. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2015)
This book brings a psychological perspective to the often overlooked and understudied topic of women's experiences of migration, covering topics such as memory, place, language, race, social class, work, violence, motherhood, and intergenerational impact of migration.